The role of the C5a-C5aR pathway in iron metabolism and gastric cancer progression - Qinxue Ni; Hong Yang; Hang Rao; Liyong Zhang; Mengyuan Xiong; Xiao Han; Boshao Deng; Lulu Wang; Jian Chen; Yan Shi (Frontiers in Immunology)
Gastric cancer continues to be a leading global health concern, with current therapeutic approaches requiring significant improvement. While the disruption of iron metabolism in the advancement of gastric cancer has been well-documented, the underlying regulatory mechanisms remain largely unexplored. Additionally, the complement C5a-C5aR pathway has been identified as a crucial factor in gastric cancer development. The impact of the complement system on iron metabolism and its role in gastric cancer progression is an area warranting further investigation. Our research demonstrates that the C5a-C5aR pathway promotes gastric cancer progression by enhancing iron acquisition in tumor cells through two mechanisms. First, it drives macrophage polarization toward the M2 phenotype, which has a strong iron-release capability. Second, it increases the expression of LCN2, a high-affinity iron-binding protein critical for iron export from tumor-associated macrophages, by activating endoplasmic reticulum stress in these cells. Both mechanisms facilitate the transfer of iron from macrophages to cancer cells, thereby promoting tumor cell proliferation. This study aims to elucidate the connection between the complement C5a-C5aR pathway and iron metabolism within the tumor microenvironment. Our data suggest a pivotal role of the C5a-C5aR pathway in tumor iron management, indicating that targeting its regulatory mechanisms may pave the way for future iron-targeted therapeutic approaches in cancer treatment.